Review Of Indonesian Constitutional Court Decision Number 21-22/PUU-V/2007 Based On The Inclusive Legal Theory - Darwis, Muhammad (Universitas Islam Indonesia, 2019)
This Sovereignty and liberalization are often considered opposites. This resistance is caused by differences in the interests of the two instruments. The object of this research is the Constitutional Court Decision Number 21-22/PUU-V/2007 about judicial review of the UUPM. This study aims to review the Constitutional Court Decision based on The Inclusive Legal Theory. It addresses the research question: What is relevance of The Inclusive Legal Theory in analysing the Constitutional Court's Decision? This study uses normative legal research, which examines the Constitutional Court Decision and the UUPM. The results show that the Constitutional Court sought, in its decision, to bridge the gap between liberalization and sovereignty by returning to the interpretation of the 1945 constitution. The mechanism of legal proceedings in the Constitutional Court is still relevant to elements of the Inclusive legal theoryKeywords: Constitutional Court, Investment, The Inclusive Legal Theory.Tinjauan Yuridis atas Putusan Mahkamah Konstitusi Republik Indonesia Nomor 21-22/PUU-V/2007 Berdasarkan Teori Hukum InklusifAbstrakKedaulatan dan liberalisasi sering dianggap berlawanan. Resistensi ini disebabkan oleh perbedaan kepentingan kedua instrumen tersebut. Objek penelitian ini adalah Putusan Mahkamah Konstitusi Nomor 21-22/PUU-V/2007 tentang pengujian UUPM. Penelitian ini bertujuan untuk mengkaji Putusan Mahkamah Konstitusi berdasarkan Teori Hukum Inklusif. Permasalahan yang diajukan dalam penelitian ini adalah: Apakah relevansi Teori Hukum Inklusif dalam menganalisis Putusan Mahkamah Konstitusi? Penelitian ini merupakan penelitian hukum normatif yang mengkaji Putusan Mahkamah Konstitusi dan UUPM. Hasil penelitian menunjukkan bahwa Mahkamah Konstitusi dalam putusannya berupaya menjembatani kesenjangan antara liberalisasi dan kedaulatan dengan kembali pada penafsiran UUD 1945. Mekanisme proses hukum di MK masih relevan dengan unsur teori hukum inklusif.Kata kunci: Investasi; Mahkamah Konstitusi; Teori Hukum Inklusif.